IDENTIFICATION OF 3D LEACHATE DISTRIBUTION IN SEMARANG STATE UNIVERSITY LANDFILL - Tri Mugirahayu; Supriyadi Supriyadi; Fianti Fianti (Jurnal Sains Dasar, 2016)
Abstract Waste management system at Semarang State University (UNNES) landfill implements a system of open dumping located in Banaran, Gunungpati, Semarang City. Data from Conservation Team UNNES on December 28, 2010 about the volume of waste per day from UNNES showed that the majority of waste is organic waste. This study aims to determine of 3D distribution leachate. Resistivity geoelectrical method Schlumberger configuration is used to indicate leachate. Data collection was performed three tracks, which three tracks parallel East-West direction, with a path length of 75 m each. The profile of leachate water in the surrounding area of UNNES landfill can be observed ± 20 m depth from the surface. Data processing was performed using software Res2Dinv, Surfer 10.0, and RockWorks 15. Based on the results, resistivity of leachate is 1,87-9,9 Ωm with the direction of flow to a lower elevation areas. Keywords: geoelectrical, leachate, resistivity, Schlumberger's configuration